First record of borofutus dhakanus (boletaceae, leccinoideae) in Thailand - Sutheera Thongkantha (2018)
A new record of Borofutus dhakanus Hosen & Zhu L. Yang is reported from Chiang Mai Province, northern Thailand. The phylogenetic relationships of the Thai specimen were compared with those of the type species and allied genera from seven major subfamilies of Boletaceae. The trees were constructed using sequences of partial 28S rDNA combined with internal transcribed spacer (ITS) gene regions. The morphological characteristics of the fungus and its edibility are also discussed. Although many boletes have been documented from Thailand, most previous records are based only on morphological characters and there is an urgent need for taxonomic revision.